2020
DOI: 10.1007/s42399-019-00214-x
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Oxidative Stress Markers in Women with Endometriosis

Abstract: Endometriosis is one of the most frequent gynecological disorders defined as the existence and growth of endometrial tissue outside the uterine cavity. Aim of this study was to evaluate the level of six oxidative stress markers in the serum of patients with and without endometriosis. This study included 46 women who were undergoing laparoscopy. The participants were divided into two groups based on their laparoscopic results. Thirty-one women had visually and histopathologically confirmed endometriosis, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Endothelial dysfunction characterizes OS, which can promote the production of ROS and the reduction of NO. There is a relationship between NO and ADMA, the first reducing NO production and the second functioning as an endogenous inhibitor 37 . The formation of ADMA occurs through two complex events.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction characterizes OS, which can promote the production of ROS and the reduction of NO. There is a relationship between NO and ADMA, the first reducing NO production and the second functioning as an endogenous inhibitor 37 . The formation of ADMA occurs through two complex events.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are following the research of Augoulea and Mukti (p-value 0.007) which showed that there was a relationship between the age of menarche and the incidence of endometriosis. 11,12 According to Sampson's theory, the incidence of endometriosis can be caused by menstrual reflux whereas women who have more menstrual opportunities will be more at risk for experiencing endometriosis. 13 Women with early age of menarche (<12 years) will be exposed to estrogen longer and the possibility of menstrual reflux will be greater, thus increasing the risk of endometriosis.…”
Section: Discussionmentioning
confidence: 99%